1997
DOI: 10.1523/jneurosci.17-21-08506.1997
|View full text |Cite
|
Sign up to set email alerts
|

Neurturin and Glial Cell Line-Derived Neurotrophic Factor Receptor-β (GDNFR-β), Novel Proteins Related to GDNF and GDNFR-α with Specific Cellular Patterns of Expression Suggesting Roles in the Developing and Adult Nervous System and in Peripheral Organs

Abstract: Cloning strategies were used to identify a gene termed glial cell line-derived neurotrophic factor receptor-␤ (GDNFR-␤) related to GDNFR-␣. In situ hybridization was then used to map cellular expression of the GDNF-related trophic factor neurturin (NTN) and GDNFR-␤ mRNA in developing and adult mice, and comparisons with GDNFR-␣ and RET were made. Neurturin is expressed in postnatal cerebral cortex, striatum, several brainstem areas, and the pineal gland. GDNFR-␤ mRNA was more widely expressed in the developing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
148
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(171 citation statements)
references
References 34 publications
21
148
2
Order By: Relevance
“…Previous reports have shown the expression of NTN, RET, and GFRa-2 in the airways (17,18,29). Our results demonstrated the mRNA expression of GFRa-2 and RET in the LA-4 cell line, WT BMDCs, and spleen DCs.…”
Section: Ntn Receptors Are Expressed In Lung Tissues Dcs and Lung Esupporting
confidence: 78%
See 1 more Smart Citation
“…Previous reports have shown the expression of NTN, RET, and GFRa-2 in the airways (17,18,29). Our results demonstrated the mRNA expression of GFRa-2 and RET in the LA-4 cell line, WT BMDCs, and spleen DCs.…”
Section: Ntn Receptors Are Expressed In Lung Tissues Dcs and Lung Esupporting
confidence: 78%
“…In addition to this interaction, NTN might cross-talk weakly with the receptor GFRa-1 (16). Expression of NTN, RET, and GFRa-2 mRNAs was observed during the development of the respiratory system (17). In adult mice, NTN was detected at a moderate level in the lung alveoli and in the thymus (18).…”
mentioning
confidence: 99%
“…GDNF mRNA is highly expressed in the striatum during development (Schaar et al, 1993;Stromberg et al, 1993;Blum and Weickert, 1995;Choi-Lundberg and Bohn, 1995;Golden et al, 1999), and we have shown by quantitative analysis that its highest level of expression is on PND 2 (Cho et al, 2003), during the first phase. The receptor for GDNF, GDNF receptor ␣1 (GFR␣1), and its signaling tyrosine kinase, Ret, are both highly expressed in SNpc during development (Widenfalk et al, 1997;Yu et al, 1998). As expected for a target-derived factor, GDNF can be specifically transported retrograde from striatum to SNpc (Tomac et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…This would depend on the availability of Ret ligands and accessory proteins in the tissues aected in MEN2B. Unfortunately, even though dierent studies have been reported on the expression of Ret ligands and of the relative coreceptors (Trupp et al, 1997;Widenfalk et al, 1997), there are no data concerning MEN2B aected tissue and the derived tumours. It has been reported that GDNF stimulation of Ret autophosphorylation and activity is dependent on one of two cell-surface-associated accessory proteins, designated GDNFRa (Jing et al, 1996;Treanor et al, 1996) and GDNFRb (Suvanto et al, 1997;Baloh et al, 1997;Sanicola et al, 1997).…”
Section: Discussionmentioning
confidence: 99%